(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Today, tourism serves as the main source of income of many developing countries. The export of tourism services creates an additional demand in the economy, providing employment to the population and increasing foreign currency revenue. Through this, the tourism sector plays an important role as the driving force for economic development. This article will talk about pilgrimage tourism, one of the currently rapidly developing types of Tourism, and the resources available in our country, and it will end with the conclusion of the authors.